PENINGKATAN KETERAMPILAN MENULIS TEKS DESKRIPSI MENGGUNAKAN METODE PENGAMATAN OBJEK LANGSUNG PADA SISWA KELAS VII SMP NEGERI 27 MEDAN - Saragih, Muhammad Ajie R.; Isman, Muhammad; Salabi, Susilawati (Universitas Muhammadiyah Tapanuli Selatan, 2024)
The purpose of this research is to describe the improvement in writing descriptive texts among seventh-grade students of SMP Negeri 27 Medan by using the technique of direct object observation. The research method used in this study is classroom action research. The research subjects are the seventh-grade students of SMP Negeri 27 Medan. One of the data collection techniques used is observation, which is employed to observe changes in student behavior during learning activities using the Direct Object Observation Technique, and tests are used to evaluate how well students have acquired descriptive text writing skills from this technique. The structure of descriptive texts, the content of ideas, grammar, cohesion and coherence, as well as spelling and punctuation are research tools used in this study. The research results show that the implementation of actions in two cycles has significantly improved. Cycle I achieved an average of 79, while Cycle II achieved an average of 90.5.